THE RELATIONSHIP BETWEEN UNIVERSITY ENTRY REQUIREMENTS AND ACADEMIC PERFORMANCE OF ACCOUNTING STUDENTS IN NIGERIA (Journal of Business Management and Accounting, 2022)
Prior studies have associated the academic performance of accounting students to learning facilities and structure, learning methods and entry requirements. Although it is expected that these entry qualifications would have an impact on the students’ performance, studies have shown contradictory findings. This study was, therefore, conducted to investigate the relationship between university entry requirements and the performance of accounting students. Data were collected from the official records of 317 accounting students who graduated from three universities in Nigeria in the 2018/2019 academic session. The data was analyzed using correlation and multiple regression statistics with the aid of SPSS. The findings of this study indicate a positive and strong correlation but statistically insignificant relationship between Senior Secondary Certificate Examination (SSCE) grade in English language, Mathematics, Economics and Accounting and the final Cumulative Grade Point Average (CGPA). The implication of the findings and recommendations are provided.